ANALISIS PENGARUH UKURAN DAN KINERJA KEUANGAN PERUSAHAANTERHADAP INFORMASI MASA DEPAN - Rahmawati, Ita Nur (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
Relevant information to predict the future of the company can beexpressed through several sources, including: annual reports, interim reports,press releases, conference calls, and direct communication with analysts.Among the sources of such information widely used in research analysis is thecompany's annual report. This is because the annual report has traditionallybeen the main medium for delivering detailed information on the company'sfinancial and non-financial information. Research and discussion on theeffect of the company's performance on future information in the company'sannual report, yields several conclusions as follows:The average disclosurerate of the sample company FLI is 42.60% (below 50%), meaning there arestill many companies that are less likely to convey future information. This isdue to the pessimism of future expectations and the reluctance to reveal toomuch information that might undermine the competitive position in themarket.Company size is the only independent variable that influences futureinformation. This means large size companies tend to convey futureinformation in their annual reports. Other independent variables of companyperformance (leverage, profitability and liquidity) have no effect on futureinformation